Identifying Key Determinants of Civil Society Robustness in Southeast Asia - Amrullah, Maulana (JAS (Journal of ASEAN Studies), 2024)
The research examines the key determinants of civil society robustness in Southeast Asia, addressing a significant gap in quantitative research within the region. Utilizing the beta regression model on data spanning from 1986 to 2023, the researcher explores the impact of participatory democracy, civil liberty, political stability, the rule of law, and neopatrimonialism on civil society’s robustness. Moderating effects of GDP per capita, control of corruption, freedom of expression, and digital freedom accessibility are also considered. Findings reveal that participatory democracy and civil liberties significantly enhance civil society’s robustness, whereas political instability tends to undermine it. Surprisingly, neopatrimonialism shows a positive influence, suggesting complex adaptive strategies by civil organizations. Along with the insignificant result of the rule of law, neopatrimonialism challenges conventional views, standing out among the variables analyzed. The research contributes to understanding the multifaceted dynamics of civil society in Southeast Asia, offering insights for policymakers and Civil Society Organizations (CSOs) to foster democratic governance and social justice. It underscores the necessity for region-specific strategies acknowledging the unique political, economic, and cultural landscapes of Southeast Asian countries.